Purification of DNA-dependent RNA polymerase from Streptomyces granaticolor - Spízek, J; Rysavý, P; Klégr, M; Náprstek, J; Janecek, J (Folia microbiologica, 1983)
RNA nucleotidyltransferase (EC 2.7.7.6) of Streptomyces granaticolor was purified by precipitation with polymin P and ammonium sulphate, affinity chromatography on DNA- cellulose and gell filtration on Biogel A 1.5 m. SDS-polyacrylamide gel electrophoresis revealed 8 protein bands of molar mass ranging from 37 to 130 kg/mol. Proteins of molar mass of 130 and 120 kg/mol were identified to be beta and beta subunits, respectively. The role of other subunits of the enzyme is discussed.
Keywords: Electrophoresis, Polyacrylamide Gel; Bacterial Proteins; Chromatography, Affinity; gelová chromatografie; elektroforéza v polyakrylamidovém gelu; chemická precipitace; Streptomyces; chromatografie afinitní; Chromatography, Gel; DNA-Directed RNA Polymerases; Chemical Precipitation; DNA řízené RNA-polymerasy; bakteriální proteiny